Osmoregulatory changes in myo-inositol transport by renal cells. - Nakanishi, T (1989)
Renal medullary cells contain high concentrations of myo-inositol, sorbitol, betaine, and glycerophosphocholine, whose levels vary with urinary osmolality. Accumulation of these "compatible" organic osmolytes is believed to help the cells osmoregulate in response to the high extracellular osmolality that occurs as part of the urinary concentrating mechanism. MDCK cells (a line from dog kidney) were previously shown to accumulate myo-inositol in response to increased medium osmolality. We demonstrate here that this accumulation requires the presence of myo-inositol in the medium, implying that the myo-inositol is not synthesized by the cells but rather is transported into them from the extracellular solution. The MDCK cells contain sodium-dependent myo-inositol transporters. Relative to isotonic controls, sodium-dependent myo-inositol uptake is higher in cells exposed to increased osmolality either acutely (1-7 days) or chronically (greater than 1 year). Transport is further enhanced when the cells are cultured in myo-inositol-free medium. The transport has both high- and low-affinity components. The observed changes in transport involve changes in maximal velocity of the high-affinity component but not in its Km. We conclude that renal cells can osmoregulate by changing the number (or, less likely, the transport turnover rate) of functioning sodium-dependent myo-inositol transporters.